2002
DOI: 10.1021/ja016954m
|View full text |Cite
|
Sign up to set email alerts
|

Organic Functionalization of Carbon Nanotubes

Abstract: A very general and versatile method for functionalizing different types of carbon nanotubes is described, using the 1,3-dipolar cycloaddition of azomethine ylides. Approximately one organic group per 100 carbon atoms of the nanotube is introduced, to yield remakably soluble bundles of nanotubes, as seen in transmission electron micrographs. The solubilization of the nanotubes generates a novel, interesting class of materials, which combines the properties of the nanotubes and the organic moiety, thus offering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
799
1
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 1,211 publications
(823 citation statements)
references
References 25 publications
17
799
1
6
Order By: Relevance
“…106,107 Electronic spectroscopy showed that the band-gap transitions in the semiconducting tubes were completely disrupted at a functionalization level of 2% of the available SWNT carbon atoms. 7 Apart from the carbene chemistry, 6 97 While the side walls of the carbon nanotubes were once considered impregnable (like the fullerenes), 32,33 there is now an extensive chemistry, 7,93,94,96,97,110 and these initial studies suggest that the chemistry of the carbon nanotubes will ultimately rival that of the carbon fullerenes.…”
Section: Covalent Chemistry Of the Walls Of The Carbon Nanotubesmentioning
confidence: 99%
“…106,107 Electronic spectroscopy showed that the band-gap transitions in the semiconducting tubes were completely disrupted at a functionalization level of 2% of the available SWNT carbon atoms. 7 Apart from the carbene chemistry, 6 97 While the side walls of the carbon nanotubes were once considered impregnable (like the fullerenes), 32,33 there is now an extensive chemistry, 7,93,94,96,97,110 and these initial studies suggest that the chemistry of the carbon nanotubes will ultimately rival that of the carbon fullerenes.…”
Section: Covalent Chemistry Of the Walls Of The Carbon Nanotubesmentioning
confidence: 99%
“…For that purpose, proper chemical treatments are required to attach functional groups to filler surface which can react with the matrix [65][66][67][68][69][70]. Figure 5a-c shows three types of surface functionalization of CNT with polymer chains, hydroxyl, and carboxyl groups, respectively.…”
Section: Covalent Interactionsmentioning
confidence: 99%
“…The 1,3-dipolar addition of azomethine ylides is particularly versatile for the functionalization of CNTs [143][144][145]. This strategy is suitable for different types of CNTs (e.g.…”
Section: Cycloadditionmentioning
confidence: 99%
“…The disruption of the aromatic structure of the sidewalls of the f -SWNTs was proven by absorption spectroscopy [143]. This functionalization technique was also used to purify CNTs [147].…”
Section: Cycloadditionmentioning
confidence: 99%